Report on workshop "Marine Science Program in the 43rd Japanese Antarctic Research Expedition on a Charter Research Vessel" - Tsuneo Odate; Mitsuo Fukuchi (National Institute of Polar Research, 2002)
A workshop on "Marine Science Program in the 43rd Japanese Antarctic Research Expedition on a Charter Research Vessel" was held on 4th October 2001 at the convention hall of the National Institute of Polar Research with 30 participants. Most of the participants will join the research cruise organized by the 43rd Japanese Antarctic Research Expedition (JARE-43) using a charter vessel. One of the purposes of this workshop is to give detailed information on the JARE system. At the same time, safety guidelines for the cruise were explained. In addition, the work schedule for the cruise was revised based on detailed requests from the participants.